Surface roughness of acrylic resins used for denture base after chemical disinfection: A systematic review and meta-analysis - Florencio Costa, Rayanna Thayse; Pellizzer, Eduardo Piza [UNESP]; Egito Vasconcelos, Belmiro Cavalcanti do; Luna Gomes, Jessica Marcela [UNESP]; Araujo Lemos, Cleidiel Aparecido; Dantas de Moraes, Sandra Lucia (Wiley-Blackwell, 2021)
Objective This study aimed to systematically review the literature regarding the surface roughness of polymethylmethacrylate (PMMA) for denture bases, disinfected with different chemical agents and analyse the outcomes of the included studies. Background Various chemical disinfection protocols to clean the removable dental prosthesis are reported in the literature, however systematic reviews analysing the outcomes in the surface roughness of the PMMA are lacking. Methods The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) checklist was used to structure this systematic review. The inclusion criteria were as follows: clinical trials, in vitro studies, studies in English and studies comparing the effects of chemical disinfection products on the surface roughness of PMMA. An electronic search was performed in the following databases: PubMed/MEDLINE, Scopus and Web of Science.; we also conducted a manual search for articles published in specific journals of dental prostheses and dental materials. Results Thirteen in vitro studies in this systematic review and meta-analysis. According to the meta-analysis, the effects of 0.5% (P = .32; MD: 0.06; CI: -0.05 to 0.17; heterogeneity: P I-2 = 92%) and 1% NaOCl solutions (P = .27; MD: 0.01; CI: -0.01. to 0.03; heterogeneity: P = .03; I-2 = 55%) did not statistically differ between the groups studied. Effects of alkaline peroxide were statistically significant (P = .0009; MD: 0.01; CI: 0.01-0.02; heterogeneity: P = .004; I-2 = 65%), suggesting that it promotes deterioration of the PMMA surface. Conclusion The alkaline peroxide, when used as a disinfectant, generated changes on the surface roughness of PMMA and should be used with caution; however, NaOCl, even at different concentrations, caused fewer changes on the surface of the denture base.
Keywords: acrylic resin; chemical disinfection; surface roughness